Study of Spatial Use Control Management in Canggu Village, Badung Regency, Bali, Indonesia - Ida Bagus Surya Suamba; Ngakan Ketut Acwin Dwijendra (International Journal of Engineering and Emerging Technology, 2021)
From an environmental perspective, implementation and awareness of environmental sustainability are translated into sustainable development policies. To become a sustainable development, the performance of development must consider environmental, social, and economic factors based on living resources that ensure the quality of life of present and future generations. The rapid development of the city will always be followed by population growth. It will lead to land-use change, especially in areas that have potential land values ??for development. The Regional Government's role in controlling the conversion of land functions is by determining the allocation of agricultural land for food crops. However, the community often responds to this directive as discriminatory treatment because of restrictions on the right to build on their land, which is different from other people's land in areas designated for settlement and tourism. There is an indication of a common form of space utilization control. Besides, the principle of justice is not created for the people who own land for agricultural purposes. In terms of utilization, land allocated for agriculture cannot build buildings that are not following their original function, but landowners' incentives are not optimal. Likewise, investors who make villas and restaurants on land designated for agriculture are not subject to appropriate disincentives. This phenomenon that occurs in Canggu Village reflects that the control of spatial use listed in the RTRW direction of Badung Regency does not yet have the principles of justice and the principles of sustainable development. Concerning the preceding, as an effort to overcome the phenomenon while preventing further similar phenomena from occurring and protecting the values ??of social justice in society, management of spatial use control is required, especially on land designated for food crop agriculture.